Water scarcity, food production and dietary choices of rural populations in Limpopo Province :a study of Musina Local Municipality - Mokgwathi, Zanele (My University, 2018)
ii DECLARATION I, Zanele Mokgwathi, declare that this research report, apart from the contributions mentioned in the acknowledgements, is my own work, unaided work. It is being submitted for the Degree of Master of Science by coursework and research report to the University of the Witwatersrand. It has not been submitted before for any degree or examination at any other University. (Signature of Candidate) ………………day of……………………………………2018 iii ABSTRACT South Africa continues to experience major challenges such as increased poverty, high levels of unemployment and in recent years, drastic increases in food and fuel prices. In addition to these challenges, rural households in South Africa must contend with the challenges of water availability. The Limpopo Province of South Africa is one of the regions that has been negatively affected by both economic and physical water scarcity. For rural households in Limpopo, the lack of water does not only threaten food production but also threatens rural health, employment and livelihoods, thereby, increasing vulnerability to food insecurity and increasing poverty. In view of this, there is a need to understand and unpack the complex relationship between water availability and dietary choices in order to reduce the vulnerability of rural households to food insecurity. This study sought to understand the impacts of water scarcity on the dietary choices of rural households in the Limpopo Province in Musina. This was achieved by exploring the different adaptive measures that households in Musina implement to cope with water scarcity. The primary aim of this research was to investigate the impacts of water scarcity on dietary choices of rural populations in Musina District, Limpopo. To achieve this aim, two secondary objectives were formulated. The first objective was to create an inventory of the impacts of water scarcity on livelihood choices. Second objective, to identify intervention entry points on building the adaptive capacity and resilience of rural households. A review of the literature was undertaken to lay the foundation for key concepts such as water scarcity, food production and dietary choices. The literature study revealed that water scarcity is one the severe challenges that rural populations in Limpopo are faced with and it has a significant impact on food security. To address the set objectives for this study, interviews were administered using a structured questionnaire as a guide. Only the household heads were interviewed, and the questionnaire consisted of open- and closed-ended questions. The respondents were selected by means of purposeful sampling technique and for analysis, only data collected from 175 usable interviews has been presented in this report. This study employed a mixed method approach as the core research methodology. The responses obtained were subjected to statistical analyses. The research findings suggest that rural households in Musina experience challenges with accessing water. The contributing factors to this challenge include high water prices and poor management of water infrastructure. Many households in Musina adapt to lack of water availability by buying water or walking to other villages in search of water. Water scarcity has an impact on food production and ultimately dietary choices. Households adapt to decreased food production and dietary choices by spending more money on food in order to ensure access. However, the respondents profile variables such as size of households, age and employment status of the household head were identified as contributing factors to vulnerability in the Musina location. In conclusion, an adjustment/change in the free basic water provision policy is recommended. This is because water availability has numerous benefits for the people of Musina, especially in terms of food security, with subsequent linkages to all other dimensions of livelihoods. This study has added to the empirical body of water scarcity, food production and dietary choices in South Africa and the world at large.
A research report submitted to the Faculty of Science, University of the Witwatersrand, in partial fulfilment of the requirements for the Degree of Master of Science by Coursework and Research Report. Johannesburg, 2018
Keywords: Irrigation farming; Irrigation water; Rural poor